2015
DOI: 10.1016/j.foodchem.2015.03.037
|View full text |Cite
|
Sign up to set email alerts
|

NMR approach for monitoring post-mortem changes in Atlantic salmon fillets stored at 0 and 4°C

Abstract: High resolution NMR technique has been used to monitor post-mortem changes in salmon (Salmo salar) fillets upon storage at 4 and 0°C. Thirty-one different fish metabolites influencing freshness and taste properties have been unequivocally assigned by NMR using either available standard compounds or ad hoc acquired 2D (1)H-(1)H TOCSY and (1)H-(13)С HSQC spectra. The monitored fish metabolites include amino acids, dipeptides, sugars, vitamins, biogenic amines, as well as different products of the ATP degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 26 publications
7
65
0
8
Order By: Relevance
“…This technique is also powerful for evaluating the quality of fish such as gilt-head bream (Sparus aurata) (Picone et al, 2011), mullet roes (Piras, Scano, Locci, Sanna, & Marincola, 2014), and Atlantic salmon fillets (Shumilina, Ciampa, Capozzi, Rustad, & Dikiy, 2015). It is particularly interesting to note that the metabolomics approach has also been used in differentiating of small-molecule metabolic profiles between two grades of crab paste (Ye et al, 2012) and revealing the metabolic response of crab to elevated level of carbon dioxide (Hammer, Pedersen, & Størseth, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This technique is also powerful for evaluating the quality of fish such as gilt-head bream (Sparus aurata) (Picone et al, 2011), mullet roes (Piras, Scano, Locci, Sanna, & Marincola, 2014), and Atlantic salmon fillets (Shumilina, Ciampa, Capozzi, Rustad, & Dikiy, 2015). It is particularly interesting to note that the metabolomics approach has also been used in differentiating of small-molecule metabolic profiles between two grades of crab paste (Ye et al, 2012) and revealing the metabolic response of crab to elevated level of carbon dioxide (Hammer, Pedersen, & Størseth, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many applications have been reported in the literature showing the potential of an NMR-based approach to investigate the geographical origin, quality control, and processing of foodstuff [33,34,35]. In addition, different fish metabolites determining fish quality, taste, etc., may be simultaneously monitored and qualitatively described, making NMR spectroscopy a valid (and in many aspects, unique) tool to characterize the metabolic profile and properties of fishes [36,37]. A further advantage of NMR-based approaches is simpler and more direct sample preparation compared with that required for other analytical methods, which may involve derivatization or column chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…When we calculated the Gini impurity, 58,59 we found that the models were best explained by the NMR-based host metabolic proles, 60,61 followed by the inorganic elements in the sh gut contents, and least by the gut microbial community. The most important variables identied for the discrimination model were the metabolites of the muscle tissue such as glycine, histidine, hypoxanthine, and taurine (Fig.…”
Section: Discrimination Modeling Of Ecosystems From Integrated Sh Mementioning
confidence: 97%